Intraoral approach for surgical treatment of Eagle syndrome - Gomes de Souza Carvalho, Abrahao Cavalcante; Magro Filho, Osvaldo [UNESP]; Garcia, Idelmo Rangel [UNESP]; Esmeraldo de Holandac, Marcelo; Sampaio de Menezes, Jose Maria (Churchill Livingstone, 2009)
Eagle syndrome is symptomatic elongation of the styloid process, or calcification of the stylomandibular ligament. Difficulty with deglutition. phonation. cervical movement. and the sensation of a foreign body in the oropharynx are all symptoms of this syndrome. Its treatment consists of partial removal of the styloid process. leaving it within the range of normality. We describe the technique, report it case, and point Out Sortie of the advantages. such as the simplicity of the procedure, reduced operating time, and lack risks of operative complications. (C) 2008 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Eagle syndrome; Intraoral approach; Styloid process